Effect Of Graphite And Nbc On Mechanical Properties Of Aisi304 Binded Wc - Tran , Bao Trung (2013)

(untitled)
This work studies the role of AISI304 stainless steel as a Co replacement binder for WC-based hardmetals. WC-AISI304 hardmetal powders were produced from raw powders (WC and AISI304) by mechanical alloying technique. The hardmetal powders were then sintered by two sintering methods; vacuum sintering and PHIP sintering. To improve mechanical properties of sintered samples, graphite (Cgr) and NbC were added prior to milling. The results show that -phase (Fe3W3C) formed in the sintered samples during sintering. Cgr addition has enabled to reduce the formation of -phase. As this phase was eliminated, both hardness and fracture toughness of sintered sample were improved. WC grain growth can be inhibited by the addition of NbC. Increasing NbC content led to an increase of hardness but reduce fracture toughness of sintered samples. Besides that, this work also show a higher potential of PHIP in generating higher density of sintered samples compared to vacuum sintering, and hence, improving mechanical properties of WC-AISI304 hardmetals. The Vickers hardness of WC-10AISI304-2Cgr-xNbC (x = 1 - 5) hardmetals produced is in range of 1600 to1660 kg/mm2 and fracture toughness, KIC, from 8.7 to 8.3 MPa.m1/2 by vacuum sintering. However, the same samples produced via PHIP sintering gave the Vickers hardness from 1640 to 1820 kg/mm2 and fracture toughness, KIC, from 10 to 7.3 MPa.m1/2. These values of hardness and fracture toughness are in the intermediate range compared to other systems provided by literatures. The results indicate that AISI304 could be proposed to replace Co binder in order to fabricate cutting inserts.